1988
DOI: 10.1080/00102208808923996
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Combustion-Chamber Deposit Thermal Behavior Utilizing Optical RadiationMeasurements in a Fired Engine

Abstract: An infrared radiometer, which incorporated three optical paths and operated between 3.5-4.0 I'm, was used to obtain transient surface temperatures in a fired engine. An integrated form of the equation of radiative transfer was applied to each optical path allowing gas emission, gas absorption and deposit surface radiation within the combustion-chamber to be characterized during a single cycle. Measurements of a simulated deposit were made at various temperatures and spark advance with the engine fired on metha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…This consideration is necessary especially in materials that contain low volumetric heat capacity which would allow fast changes in temperature, and low thermal conductivity which would enable a reduction in overall heat transfer and an increase in surface temperature during combustion and expansion. In both analytical (Wallace, Way, & Vollmert, 1979) (Morel, Fort, & Blumberg, 1985) (Anderson & Prakash, 1985) (Kosaka, et al, 2013) and experimental (Furuhama & Enomoto, 1987) (Harder & Anderson, 1988) (Aoki, et al, 2015) studies, a non-negligible swing in surface temperature throughout the engine cycle was observed with increasing insulation. This poses unique possibilities and challenges over the concept of a steady, elevated temperature and was fundamentally different from the net-zero heat transfer model with respect to the processes occurring in-cylinder.…”
Section: Temperature-swing Insulation In Literaturementioning
confidence: 99%
“…This consideration is necessary especially in materials that contain low volumetric heat capacity which would allow fast changes in temperature, and low thermal conductivity which would enable a reduction in overall heat transfer and an increase in surface temperature during combustion and expansion. In both analytical (Wallace, Way, & Vollmert, 1979) (Morel, Fort, & Blumberg, 1985) (Anderson & Prakash, 1985) (Kosaka, et al, 2013) and experimental (Furuhama & Enomoto, 1987) (Harder & Anderson, 1988) (Aoki, et al, 2015) studies, a non-negligible swing in surface temperature throughout the engine cycle was observed with increasing insulation. This poses unique possibilities and challenges over the concept of a steady, elevated temperature and was fundamentally different from the net-zero heat transfer model with respect to the processes occurring in-cylinder.…”
Section: Temperature-swing Insulation In Literaturementioning
confidence: 99%